Tick tick (commodity) boom: condicionantes das propostas de taxação de commodities na América Latina - Haag, Valentina Tâmara (2022)
In this Master’s thesis, I examine the explanatory capacity of the commodity boom as an incentive for taxation proposals in Latin America by tackling the following puzzle: what is the relationship between the commodity price boom and taxation proposals in this sector? My main hypothesis is that periods of high prices encouraged proposals of commodity taxation in Latin America. To assess the strength of this hypothesis, I propose a comparison with other variables that potentially explain taxation proposals. These incentives for taxation are: government ideology (left/right, economic orientation and populism), crises (political and economic), social (politicization of the agenda) and economic (exposure to prices) relevance of the commodity sector for each case. An empirical analysis supports the argument that the boom acts as incentive, however, its role is conditioned by the presence of two other variables: government ideology and high exposure to commodity prices. In short, my main finding is that periods of high prices encourage taxation proposals of the Latin American commodity sector when they coincide with leftist governments in countries highly exposed to price volatility. To conduct this research, I applied a comparative methodology assisted by procedures matrix data analysis and medium-C case studies of a set of positive, negative and atypical cases. For the dissertation, a database of 53 Latin American governments (2000-2021) coded according to the taxation incentives tested by my model. The main contributions of this thesis were the construction of a large dataset, which is available for other applications and tests, and the discussion of the role of opportunity in commodity taxation.